Knowledge Authoring in E-learning: An Ethicultural Diagnosis - Silva, Nuno Sotero Alves da (2014)
The intent of this manuscript is to emphasize if distributed knowledge creation within higher education encompasses an ethical and cultural sensitivity. This research problem resumes the ethical and social dilemmas that e-learning evolution imposes to knowledge “creators”. For that, under enquiry will be empirical examples through Silva’s framework, namely the knowledge/content management layer. Therefore, this contribution is divided into five sections: theoretical assumptions; knowledge dimensions (political, economical, social/cultural and digital); knowledge development cycle; knowledge authoring in e-learning; and discussion (ethicultural: the meaning, framework design and practical examples).